The Effectiveness of Preview, Question, Read, Summary and Test (PQRST) Method to Improve Students’ Reading Comprehension at SMA Islam Roudlotun Nasyiin Mojokerto - Lus Firdaus Zakiya; Yenny Triariani (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
In our daily lives, language plays a crucial function as a communication tool. One of the most crucial receptive abilities in language learning and instruction is reading. If you are still working on your receptive skills, it will be challenging to develop your productive skills. Finding information in a book and using it to make a decision is the process of reading. PQRST is a teaching method that has been demonstrated to improve readers' comprehension and retention of material. The text is that first-graders in senior high school should be proficient in is narrative. Put another way, a narrative text is a composition of written work whose purpose is to assist the reader in understanding the importance of the story. The research aims is to determine the effectiveness of the PQRST Method in teaching reading comprehension. This research was conducted in class X of SMA Islam Roudlotun Nasyiin, Mojokerto. This research use pre-experimental quantitative research method which is carried out in 1 class by giving pre-test and post-test. The subject of this research is 1 class with 20 students. The data collected was from pre-test and post-test. Due to the sample size being less than fifty, the Saphiro-Wilk normalcy test was utilized. There is a substantial difference, as evidenced by the T test results, which indicate that if sig. (2-tailed) < 0.05, HO is rejected and Ha is accepted.